Does immigration policy affect the education-occupation mismatch? Evidence from Australia - Massimiliano Tani (Institute for the Study of Labor (IZA), 2012)
This paper analyses the impact of a change in Australia's immigration policy, introduced on 1st July 1999, on migrants' probability of being over-/under-educated or correctly matched. The policy change consists of stricter entry requirements about age, language ability, education, and work experience. The results indicate that those who entered under more stringent conditions - the second cohort - have a lower probability to be overeducated and a correspondingly higher probability of being better matched than those in the first cohort. The policy change appears to have reduced the incidence of over-education among women, enhanced the relevance of being educated in Australia to be correctly matched, and attracted a higher proportion of immigrants that were already under-utilised (or over-achieving) in their home countries. Overall, the policy appears to have brought immigrants that reduced the over-under-education of Australia's labour market.
Keywords: C34; J24; J61; 330; immigration policy; over- and under-education; migration; Migrationspolitik; Qualifikationsbedarf; Migranten; Arbeitsmarkt; Matching; Australien